Lignocellulolytic Enzymes by Aspergillus sp. A1 and Bacillus sp. B1 isolated from gut of Bulbitemes sp. in solid state fermentation using sawdust as substrate - Noratiqah Kamsani, 1987-, author; Madihah Md. Salleh, 1967-, supervisor; Adibah Yahya, supervisor; Chong, Chun Shiong, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Biosains)) - Universiti Teknologi Malaysia, 2017